2000
DOI: 10.1159/000013891
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Deterioration of Central Components of Auditory Brainstem Responses during Postnatal Development of the Myelin Mutant <i>taiep</i> Rat

Abstract: Auditory brainstem responses (ABRs) were evaluated during the postnatal development (P10–P180) of taiep rats, neurological mutants characterized by early abnormal myelin development and subsequent demyelination of the CNS. The disorder is produced by an autosomal recessive mutation trait that affects the oligodendrocytes but not the Schwann cells. After onset of ABRs (P12–P14), taiep rats and their nonaffected heterozygous littermates that served as controls showed a similar pattern of maturation for wave I. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…A slight decrease in central nerve conduction velocity was, however, evident from increased latencies in ABRs. Similar increases were found in demyelinating mouse models (Roncagliolo et al, 2000) and in patients with subclinical forms of CNS myelopathies (Robinson and Rudge, 1975;Starr, 1978;Elidan et al, 1982).…”
Section: Discussionsupporting
confidence: 72%
“…A slight decrease in central nerve conduction velocity was, however, evident from increased latencies in ABRs. Similar increases were found in demyelinating mouse models (Roncagliolo et al, 2000) and in patients with subclinical forms of CNS myelopathies (Robinson and Rudge, 1975;Starr, 1978;Elidan et al, 1982).…”
Section: Discussionsupporting
confidence: 72%
“…For example, Huttenlocher and de Courten [25] found that the greatest increases in synaptogenesis in the occipital cortex occur between 2.5 and 8 postnatal months; however, this process is relatively slower in the frontal cortex where synapse formation does not reach its maximum density until after 15 postnatal months. Third, influences of myelin development on the morphology of waveforms have been demonstrated in animal studies [26], showing that brain responses can be impaired if the brain is exposed to carbon monoxide during the developmental stage of myelination [27]. Moreover, the number of neurons involved in the sensory processes may vary at different ages.…”
Section: Morphological Changes Of Erp Componentsmentioning
confidence: 98%
“…Myelination of the nerve fibers is executed by oligodendrocytes [1] and animals with abnormal myelin development or demyelination have severely impaired pathways [2], leading to behavioral defects such as changes in locomotive function or impaired coordination [3]. Unfortunately, in the postnatal development of the CNS of experimental animals, the temporal sequence of myelination has been largely neglected.…”
Section: Introductionmentioning
confidence: 99%